From preparedness to adaptation: Swiss hospitals’ communication strategies in a prolonged crisis - Diviani, Nicola; Fiordelli, Maddalena; Ort, Alexander; Rubinelli, Sara (Frontiers in Communication, 2025)
BackgroundEffective communication is essential during health crises to maintain operational clarity, staff engagement, and public trust. While existing models emphasise centralised crisis response and structured messaging, few studies examine how hospital communication evolves across different phases of a prolonged emergency.ObjectiveThis study explored how Swiss hospitals adapted their internal and external communication strategies during the COVID-19 pandemic, identifying key challenges, approaches, and lessons for future preparedness.MethodsWe conducted a retrospective qualitative study based on semi-structured interviews with 18 communication leaders from public hospitals across Switzerland. Thematic analysis was used to identify evolving communication strategies, challenges, and adaptations over time.ResultsFour dynamic phases emerged: preparedness and early onset, peak crisis response, stabilisation, and prolonged crisis adaptation. Communication strategies shifted from rapid internal coordination and leadership visibility to targeted digital engagement and staff support. Hospitals implemented structured messaging loops, leveraged mobile platforms, engaged in proactive media outreach, and introduced psychological support and recognition campaigns. Over time, they also refined communication protocols and reduced message frequency to avoid overload. Despite these efforts, challenges remained in managing decentralised coordination, sustaining morale, and countering misinformation.ConclusionHospital communication during COVID-19 required continuous adaptation. Beyond disseminating information, effective strategies fostered connection, reassurance, and trust. Our findings highlight the need for communication systems that are both structured and flexible, grounded in resilience, and integrated into broader institutional crisis planning. These insights inform future communication frameworks for healthcare institutions facing prolonged emergencies.